Influence of Germanium Sulfide on the Structure, Ag-Ion Conductivity and Stability of Glasses in the GeS2-Sb2S3-AgI System - Viktor Markov; Talib Farziev; Nikita Dybin (Solids)
This article discusses the superionic glassy GeS2-Sb2S3-AgI system with mobile silver ions as a material for creating new energy-efficient solid-state ion emitters. The effect of replacing silver iodide with germanium sulfide on the structure of the electrolyte, activation energy of diffusion, and specific ionic conductivity was studied. Electrolytes (2.5 + x)GeS2-27.5Sb2S3-(70 − x)AgI, x = 0, 5, 10, 15 were synthesized using the melt-quenching technique in evacuated quartz ampoules. The temperature dependence of conductivity and glass stability parameters (Hruby’s, Weinberg’s and Lu–Liu’s) were determined for them, and the mechanism for increasing glass-forming ability was clarified. It was shown that the presence of iodine in a germanium structural unit is more preferable than in an antimony structural unit; germanium structural units compete for iodine, reducing the number of SbI3 crystallization centers and chain terminations, resulting in additional structural connectivity and stability. It was shown that when silver iodide was replaced by germanium sulfide, the decrease in conductivity due to the reduction in charge carriers was less than expected due to the expansion of the conduction channels.